Rapid Retrograde Tyrosine Phosphorylation of trkA and Other Proteins in Rat Sympathetic Neurons in Compartmented Cultures - Senger, Donna L. (The Rockefeller University Press, 1997)
According to the current theory of retrograde signaling, NGF binds to receptors on the axon terminals and is internalized by receptor-mediated endocytosis. Vesicles with NGF in their lumina, activating receptors in their membranes, travel to the cell bodies and initiate signaling cascades that reach the nucleus. This theory predicts that the retrograde appearance of activated signaling molecules in the cell bodies should coincide with the retrograde appearance of the NGF that initiated the signals. However, we observed that NGF applied locally to distal axons of rat sympathetic neurons in compartmented cultures produced increased tyrosine phosphorylation of trkA in cell bodies/ proximal axons within 1 min. Other proximal proteins, including several apparently localized in cell bodies, displayed increased tyrosine phosphorylation within 5–15 min. However, no detectable (125)I-NGF appeared in the cell bodies/proximal axons within 30–60 min of its addition to distal axons. Even if a small, undetectable fraction of transported (125)I-NGF was internalized and loaded onto the retrograde transport system immediately after NGF application, at least 3–6 min would be required for the NGF that binds to receptors on distal axons just outside the barrier to be transported to the proximal axons just inside the barrier. Moreover, it is unlikely that the tiny fraction of distal axon trk receptors located near the barrier alone could produce a measurable retrograde trk phosphorylation even if enough time was allowed for internalization and transport of these receptors. Thus, our results provide strong evidence that NGF-induced retrograde signals precede the arrival of endocytotic vesicles containing the NGF that induced them. We further suggest that at least some components of the retrograde signal are carried by a propagation mechanism.